The effect of using a diode laser as an adjunction to the non-surgical treatment of chronic periodontitis in orthodontic patients - A. Abdulmatloba, Malek; M. Gondib, Khalid; R. Elharathia, Anas; K. Almagrahia, Warda; O. Mahfouda, Salma (Libyan Journal of Science &Technology, 2024)
The use of a laser to accelerate the wound healing process has been extensively studied; however, only a few reports in the area of periodontics being available. The literature regarding laser therapy is inconclusive, some studies showing beneficial effects, while others reported no additional effect at all. Investigations failed to demonstrate effects, possibly because of the large choices of parameters. The purpose of this study is to assess the potential effect of the clinical application of diode laser as an adjuvant for mechanical periodontal treatment in orthodontic patients. Sixteenorthodontic patients (nine females and seven males) with a mean age of 27years±4.41, with a good systemic condition, have been recruited in this study. They were diagnosed with mild-moderate chronic periodontitis (PPD ≥ 4mm). Forty teeth in two different quadrants (contralateral matched pairs)have been studied and the selected sites were randomly categorized into two groups; Group I (Control or SRP group), Group II (Test or SRP + Laser group). Firstly, the selected cases received conventional mechanical debridement, after which the experimental teeth were randomly allocated to either test or control groups. All teeth subjected to scaling, root planing (SRP), and teeth assigned to the test group (SRP + Laser) were irradiated with the 660 nm diode laser twice for 30 s, in two isolated appointments, 1 week apart. The laser technique was used in the continuous mode, with 100mW power output. Clinical parameters included bleeding on probing (BOP) and probing pocket depth (PPD) were measured and data collected at baseline, 2 weeks, 4 weeks, and 6 weeks after therapy. The clinical comparison was performed throughout the study period, to show the actual performance of the two therapeutic modalities. Statistical analysis revealed a significant reduction of the clinical parameters (BOPand PPD) in both groups at two, four, and six weeks when compared to the baseline. However, no significant differences have been found between the two groups throughout the study period. The outcomes are in agreement with some previous studies, and disagreement with others. In summary, non-surgical periodontal therapy is still considered the gold standard for periodontal treatment. Application of 660-nm diode laser is a non-invasive technique and no operative or postoperative complications have been reported by the subjects.